PENGERING TANGAN OTOMATIS DILENGKAPI PESAN SUARA BERBASIS MIKROCONTROLER AT MEGA 16 - , FEBRIAN DWI K ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Technology today is growing, so a lot of equipment or machinery that was created to facilitate the work of people, diataranya is a tool for drying hands automatically include voice mail. Problems arise when the wash and dry their hands with a cloth or tissue, because the fabric used to dry hands and less hygienic tissue itself is made of wood that growth is not proportional to its use. With this tool it is guaranteed hygiene, conserve natural resources and got a voice message that people always put hygiene. This tool can dry your hands with a maximum distance of 12 cm below it. Microcontroller entire working set of components, LCD is used as instructions for using the tool, while the sound recorder to record and play voice messages. Source voltage is 12 volts electronics system which then regulated using a constant voltage regulator in order.